Penerapan Sistem Reward dan Punishment Terhadap Disiplin Belajar Siswa Kelas 2 Di MI Diponegoro - Nafidz, Arya Hanan (Maliki Interdisciplinary Journal, 2025)
The purpose of this study is to find out how the role of teachers in classroom management of a learning at MI Diponegoro. This research was carried out through a qualitative approach. The data was collected through interviews and observations. This data is analyzed through 4 stages, namely planning, implementation of actions, observation, and reflection. This study concludes how important the role of teachers is in creating discipline in the learning process of students at MI Diponegoro. At MI Diponegoro, teachers apply a reward and punishment system to students, so that they are able to be well conditioned. And also the teachers in this madrasah have a forum with parents in assisting students, so that they can be more conditioned or disciplined in learning.